Continuous-Flow Chemistry in the Research Laboratory Modern Organic Chemistry in Dedicated Reactors at the Dawn of the 21st Century - Glasnov, Toma (Springer International Publishing : Imprint: Springer, 2016)
This book presents a short introduction to the historical background to the field, the state of the art and a brief survey of the available instrumentation and the processing techniques used. The following major areas of interest in synthetic, organic and medicinal chemistry are elaborated on: transition-metal catalyzed reactions, organocatalytic transformations, heterocyclic synthesis, and photochemical reactions. Finally, selected applications in industry are also discussed. With its ample presentation of examples from recent literature, this is an essential and reliable source of information for both experienced researchers and postgraduate newcomers to the field.